Pertanggungjawaban Hukum Bank atas Kelalaian Melaksanakan Identifikasi dan Verifikasi dalam Penyelenggaraan Layanan Perbankan Digital - Tanudiharja, Gabriella Fransisca; Handayani, Tri; Yuanitasari, Deviana (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research highlights the obligation of banks to identify and verify prospective or existing customers when conducting business relationships through digital services, as an implementation of the prudential principle based on POJK No. 21 of 2023. The purpose of this research is to explain these identification and verification obligations and to elaborate on the bank's liability in the event of errors and/or negligence in performing these duties in accordance with POJK No. 22 of 2023. The method used is normative juridical method with a literature-based approach, the study analyzes relevant legal materials. The research show that banks are liable for customer losses due to improper identification and verification but may be exempt if contributory negligence by the customer is proven. The research recommends strengthening prudential practices and internal oversight in Indonesian banking.